Dysregulation of the Intrarenal Vitamin D Endocytic Pathway in a Nephropathy-Prone Mouse Model of Type 1 Diabetes - Fowlkes, John L. (Hindawi Publishing Corporation, 2011)
Microalbuminuria in humans with Type 1 diabetes (T1D) is associated with increased urinary excretion of megalin, as well as many megalin ligands, including vitamin-D-binding protein (VDBP). We examined the DBA/2J diabetic mouse, nephropathy prone model, to determine if megalin and VDBP excretion coincide with the development of diabetic nephropathy. Megalin, VDBP, and 25-hydroxy-vitamin D (25-OHD) were measured in urine, and genes involved in vitamin D metabolism were assessed in renal tissues from diabetic and control mice at 10, 15, and 18 weeks following the onset of diabetes. Megalin, VDBP, and 25-OHD were increased in the urine of diabetic mice. 1-α hydroxylase (CYP27B1) mRNA in the kidney was persistently increased in diabetic mice, as were several vitamin D-target genes. These studies show that intrarenal vitamin D handling is altered in the diabetic kidney, and they suggest that in T1D, urinary losses of VDBP may portend risk for intrarenal and extrarenal vitamin D deficiencies.